1997
DOI: 10.1080/713693391
|View full text |Cite
|
Sign up to set email alerts
|

On the Appropriate Use of Location Quotients in Generating Regional Input-Output Tables: A Comment

Abstract: BRAND S., (1997) On the appropriate use of location quotients in generating regional input-output tables: a comment, Reg. Studies 31, 791-794. This paper questions the FLQ as a useful contribution to the methods of constructing hybrid regional input-output tables. The genre of non-survey location estimators have a weak theoretical base and a poor empirical pedigree. The FLQ offers little to remedy the fundamental deficiencies of the genre. Research funds would be much more effectively employed in any form of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
0
13
0
4
Order By: Relevance
“…Thus the ® ndings show that the inclusion TNE )}] b is used to adjust for regional size. On this and of a measure of regional specialization is not helpful in related issues, see the exchange betweenBRAND, 1997, andWEBBER, 1997. producing more accurate simulations. 4.…”
mentioning
confidence: 97%
“…Thus the ® ndings show that the inclusion TNE )}] b is used to adjust for regional size. On this and of a measure of regional specialization is not helpful in related issues, see the exchange betweenBRAND, 1997, andWEBBER, 1997. producing more accurate simulations. 4.…”
mentioning
confidence: 97%
“…() posit an inverse relationship between regional size and the propensity to import from other regions. Brand () criticized the initial FLQ formula (see Flegg et al. ) on the grounds that the regional scalar λ δ was very insensitive to variations in the relative size of the regional economy to the national economy.…”
Section: Methodsmentioning
confidence: 99%
“…Flegg et al (1995) posit an inverse relationship between regional size and the propensity to import from other regions. Brand (1997) criticized the initial FLQ formula (see Flegg et al 1995) on the grounds that the regional scalar λ δ was very insensitive to variations in the relative size of the regional economy to the national economy. Based on this criticism, Flegg and Webber (1997) reformulated the FLQ to become more sensitive to variations in the relative size of regions.…”
Section: Location Quotientsmentioning
confidence: 99%
“…The spatial Gini coefficient (Ellison & Glaeser, 1994, 1997, which is also known as Ellison-Glaeser index, is a much easier index than indices discussed above. During their study on geographic concentration in the USA, the authors found that, as per their index analysis, if the coefficient value is 0, it implies that the industry is equally distributed across the regions.…”
Section: Literature Reviewmentioning
confidence: 99%